Incidence of Aspiration Pneumonia in Patients with Altered Consciousness Admitted in DMCH (Journal of Medicine, 2014)
Background: Aspiration Pneumonia is a common complication in patients with altered consciousness if general supportive care is not taken properly. There is no national study on incidence of aspiration pneumonia in hospitalized patients with altered consciousness. This study was done to see the incidence of aspiration pneumonia in patients with altered consciousness admitted in a tertiary care hospital in our country. Methods: This was a prospective observational study conducted among the 50 adult patients of aspiration pneumonia with altered consciousness admitted in the medicine department of DMCH, during January 2010 to December 2010. Aspiration pneumonia was confirmed by clinical examination and laboratory investigations. Assessment of altered conscious patient was done by application of the Glasgow Coma Scale. Case record forms with appropriate questionnaire were filled for all patients. Results: The mean (±SD) age was 38.9±17.3 years. Maximum numbers (24.5%) of patients were found in the age group of 51-60 years. Male female ratio was 3:1. Fever, chest pain and productive cough were the most common clinical features. Stroke (64%), Encephalitis (16%) and Hepatic encephalopathy (16%) were found as main precipitating factors.DOI: http://dx.doi.org/10.3329/jom.v15i1.19853 J Medicine 2014; 15: 14-17